1993
DOI: 10.1164/ajrccm/147.6_pt_1.1562
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin L Activity Is Increased in Alveolar Macrophages and Bronchoalveolar Lavage Fluid of Smokers

Abstract: Elastinolytic enzymes derived from alveolar macrophages (AM) are considered to play an important role in the development of emphysema associated with cigarette smoking. In this study, the enzyme activity and mRNA expression of cathepsin L were quantitated in AM and bronchoalveolar lavage (BAL) fluid obtained from current smokers and compared with those from nonsmokers. Activity was measured with the synthetic substrate Z-Phe-Arg-MCA combined with a novel cathepsin B inhibitor, CA-074. We found that the specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 33 publications
4
34
0
Order By: Relevance
“…This is the first evidence indicating association of Cath H expression or regulation with cigarette smoking in human lung cancer and is consistent with previous studies revealing an increase of Cath B and L activity in lung tissue of smokers (Knoch et al, 1994;Werle et al, 1995), in their alveolar macrophages and alveolar lavage fluid (Chang et al, 1986;Takahashi et al, 1993) as well as in alveolar macrophages and bronchoalveolar lavage fluid of rats exposed to cigarette smoke Lesser et al, 1989;Chapman et al, 1997). Furthermore, Yukio Ishii (1991aIshii ( , 1991b clearly demonstrated that Cath H is secreted mainly with surfactant from Type II alveolar epithelial cells and alveolar macrophages of rat lung.…”
Section: Discussionsupporting
confidence: 92%
“…This is the first evidence indicating association of Cath H expression or regulation with cigarette smoking in human lung cancer and is consistent with previous studies revealing an increase of Cath B and L activity in lung tissue of smokers (Knoch et al, 1994;Werle et al, 1995), in their alveolar macrophages and alveolar lavage fluid (Chang et al, 1986;Takahashi et al, 1993) as well as in alveolar macrophages and bronchoalveolar lavage fluid of rats exposed to cigarette smoke Lesser et al, 1989;Chapman et al, 1997). Furthermore, Yukio Ishii (1991aIshii ( , 1991b clearly demonstrated that Cath H is secreted mainly with surfactant from Type II alveolar epithelial cells and alveolar macrophages of rat lung.…”
Section: Discussionsupporting
confidence: 92%
“…Cathepsins are cysteine proteases produced predominantly by macrophages and are involved in matrix remodeling and Ag processing (24). Elevated levels of active cathepsin L have been shown in the bronchoalveolar lavage (BAL) of smokers and individuals with emphysema due to the increased numbers of macrophages present, and they are thought to play an important role in the lung destruction observed in the emphysematous lung (23,25). The observation of SLPI proteolysis by cathepsins B, L, and S has raised the question of whether members of the defensin family are also susceptible to proteolytic cleavage by the cathepsins.…”
mentioning
confidence: 99%
“…Smokers have increased expression of cathepsin L in AM compared to non-smokers (Takahashi et al,1993), and also increased activity of cathepsin S in AM lysates (Reilly et al, 1991). Pro-inflammatory mediators induce expression of MMPs, such as the marked increase in mRNA for MMP12 in cultured AM by lipopolysaccharide (LPS) .…”
Section: Potential Role Of Macrophage Proteases In Emphysemamentioning
confidence: 99%